Phytochemical Analysis and Cytotoxic Activities of Hantap Leaves (Sterculia coccinea Jack) Extract - Yuliet Yuliet; Agustinus Widodo; Khildah Khaerati; Joni Tandi (Universitas Gadjah Mada, 2023)
Hantap (Sterculia coccinea Jack) has been used traditionally for various health issues, including cancer treatment. The therapeutic effects of natural ingredients are often attributed to their chemical constituents. This study aimed to analyze the phytochemical contents and cytotoxic activities of S. coccinea leaves on HeLa and MCF-7 cancer cell lines. The quantitative phytochemical analysis was carried out following standard laboratory procedures. Phytochemical compounds were identified using LC-MS/MS QTOF. The MTT assay PrestoBlue™ Cell Viability Reagent test method was used to test cytotoxic activity in the cell culture. Extraction was carried out by the maceration method using 96% ethanol as solvent. The quantitative analysis revealed that tannins were the major phytochemical constituent in the highest percentage of 72.16%, followed by alkaloids, flavonoids, and steroids, with values of 30.80, 28.66, and 2.85%, respectively. Saponins were present in the lowest percentage of 1.15%. The ethanolic extract exhibited moderate cytotoxicity on HeLa and MCF-7 cells with IC50 values of 591.00 and 578.10 µg/mL, respectively. Identification using LC-MS/MS showed the suspected compounds 5,7-dihydroxy-3-(4'-hydroxybenzyl)chromone as homoisoflavanones and kaempferide-3-O-α-L-rhamnosyl-7-O-α-L-rhamnoside from flavonol triglycosides. These results may contribute to the study on the use of leaves extract of S. coccinea for developing a chemoprevention agent.